PERANAN TINGKAT PENDIDIKAN TERHADAP KINERJA STAFF ROOM DIVISION DALAM MELAYANI TAMU DI UNHAS HOTEL AND CONVENTION - Anggun Sari Sasmita; Indonesia Indonesia; Irma Utari Mansyur (HOME : Hospitality and Gastronomy Research Journal, 2026)
This study aims to analyze the role of education level in supporting the performance of reception staff and room attendants at Unhas Hotel & Convention. The study is motivated by the limited research comparing the contribution of education level to two different positions within the Room Division, namely reception staff, who are oriented toward direct guest service, and room attendants, who are oriented toward technical-operational tasks. This research employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The informants consisted of 7 reception staff, 9 room attendants, and a supervisor, selected using purposive sampling. The data were analyzed through data reduction, data display, and conclusion drawing, with validation conducted through source triangulation, method triangulation, and member checking. The findings indicate that education level contributes differently to the two Room Division positions. For reception staff, education strengthens communication skills, understanding of service procedures, guest administration, use of work systems, and complaint handling. For room attendants, education mainly serves as a foundation for discipline, responsibility, understanding work instructions, and professional attitudes, while technical skills are developed more through training, daily work practice, and supervision. These findings show that the contribution of education to hotel staff performance is contextual and depends on job characteristics. The study implies that hotel management should design competency-based recruitment, placement, and human resource development policies that differ between reception and room attendant positions.